Online Business Marketing Communication Strategy for Seblak Nasiracook Products in Attracting Buyer's Interest - Siregar, Jaemi Karunnisyah; Alfikri, Muhammad; Muary, Rholand (International Journal of Cultural and Social Science, 2023)
This study is entitled "Seblak Nasiracook Product Online Business Marketing Communication Strategy in Attracting Buyer Interest". This research uses qualitative research methods with a descriptive approach using integrated marketing communication theory (Integrated Marketing Communication). This study aims to find out about how the marketing communication strategy used by Nasiracook occurs in doing business and online business to attract buyers, the second wants to know more about how marketing communication strategies work. The results in this study are Nasiracook using and utilizing Instagram social media and tik tok in doing marketing, building partnerships with e-commerce in doing marketing for online business, and participating in culinary festivals to do marketing and bring in new buyers.